Talempong Music in West Sumatra - Nursyirwan; Delfi Enida; Alfalah; Maisaratun Najmi (SPAFA Journal)
The ethnomusicological focus of this study is primarily directed at the musical traditions that are still alive and actively maintained by the community and its supporters. This study delves into the unwritten of realm music, especially music that is delivered orally, which is represented by the traditional metal talempong in the Minangkabau ethnic area. This study addresses issues and objectives that center on talempong as a characteristic or “icon” of traditional performing arts that develop in every village in the Minangkabau region, such as in Tanah Datar Regency; Agam Regency; Lima Puluh Kota Regency, Sijunjung Regency; and Solok Regency. The findings of the study on metal talempong music in Minangkabau reveal its significance as a cultural representation that symbolizes the Malay community in general. Talempong music serves as a key indicator of Minangkabau regional identity, recognized since ancient times throughout the entire archipelago. This study highlights interesting findings regarding the diversity of talempong existence today, emphasizing the “tuning” technique used by traditional cultural groups in Minangkabau. Where, this group relies on their senses, moods, and feelings to produce the distinctive sound of the metal talempong. In contrast, modern artists in Minangkabau approach the talempong “tuning technique” using Western diatonic instruments following established standards. Despite being influenced by modernity, traditional tuning methods persist in Minangkabau society, using a non-diatonic approach. Two striking basic techniques are the five-tone variant scale, synonymous with the Minangkabau musical tradition known as “limo Salabuan voice,” and the six-tone variant scale, associated with the Minangkabau musical tradition known as “onam Salabuan voice.”